The Influence of the Family Hope Program (PKH) Policy on Community Welfare in Kubung District, Solok Regency - Mardaus Mardaus; Afriva Khaidir (Program Pascasarjana Universitas Negeri Makassar, 2021)
The Family Hope Program and its impact on Community Welfare in Kubung District, Solok Regency, is one of the Government's policies to address poverty problems, especially meeting the health and basic education needs of children from poor families and providing assistance with conditions that must be met by participants before receiving assistance. This research was conducted with the aim of knowing the implementation of the Family Hope Program in Kubung District, Kab. Solok and to find out whether the Family Hope Program has an effect on Community Welfare in the District. Kubung District of Solok. This type of research used in this research is descriptive quantitative research to reveal facts related to the Family Hope Program and its impact on community welfare in the district. Lemur. The population in this study were all participants of the Family Hope Program in the district. Lemur. Determination of the sample in this study using purposive sampling technique, while the categories of samples taken by researchers were those who had become PKH participants and because the population in the study was difficult to reach as a whole, the number of samples was set at 61 people. To measure respondents' opinions through questionnaires regarding the events and symptoms they experienced, researchers used a Likert scale technique. And data analysis using descriptive and inferential statistical analysis with the SPSS system and data analysis through observation and interviews to strengthen the results of statistical analysis. Determination of the sample in this study using purposive sampling technique, while the categories of samples taken by researchers were those who had become PKH participants and because the population in the study was difficult to reach as a whole, the number of samples was set at 61 people. To measure respondents' opinions through questionnaires regarding the events and symptoms they experienced, researchers used a Likert scale technique. And data analysis using descriptive and inferential statistical analysis with the SPSS system and data analysis through observation and interviews to strengthen the results of statistical analysis. Determination of the sample in this study using purposive sampling technique, while the categories of samples taken by researchers were those who had become PKH participants and because the population in the study was difficult to reach as a whole, the number of samples was set at 61 people. To measure respondents' opinions through a questionnaire regarding the events and symptoms they experienced, researchers used a Likert scale technique. And data analysis using descriptive and inferential statistical analysis with the SPSS system and data analysis through observation and interviews to strengthen the results of statistical analysis. As for the categories of samples taken by researchers are those who have become PKH participants and due to the fact that the population in the study is difficult to reach as a whole, the number of samples is set at 61 people. To measure respondents' opinions through questionnaires regarding the events and symptoms they experienced, researchers used a Likert scale technique. And data analysis using descriptive and inferential statistical analysis with the SPSS system and data analysis through observation and interviews to strengthen the results of statistical analysis. As for the categories of samples taken by researchers are those who have become PKH participants and due to the fact that the population in the study is difficult to reach as a whole, the number of samples is set at 61 people. To measure respondents' opinions through questionnaires regarding the events and symptoms they experienced, researchers used a Likert scale technique. And data analysis using descriptive and inferential statistical analysis with the SPSS system and data analysis through observation and interviews to strengthen the results of statistical analysis.